Peripheral blood mononuclear cells reactivity in recent-onset type I diabetes patients is directed against the leader peptide of preproinsulin, GAD65271-285 and GAD65431-450 - Jores, Rita D.; Baldera, Davide; Schirru, Enrico; Muntoni, Sandro; Rossino, Rossano; Manchinu, Maria F.; Marongiu, Maria F.; Caria, Cristian A.; Ripoli, Carlo; Ricciardi, Maria R.; Cucca, Francesco; Congia, Mauro (Frontiers in Immunology, 2023)
T cell reactivity against pancreatic autoantigens is considered one of the main contributors to the destruction of insulin-producing cells in type 1 diabetes (T1D). Over the years, peptide epitopes derived from these autoantigens have been described in NOD mice and in both HLA class II transgenic mice and humans. However, which ones are involved in the early onset or in the progressive phases of the disease is still unclear. In this work we have investigated, in early-onset T1D pediatric patients and HLA-matched controls from Sardinia, the potential of preproinsulin (PPI) and glutamate decarboxylase 65 (GAD65)-derived peptides to induce spontaneous T cell proliferation responses of peripheral blood mononuclear cells (PBMCs). Significant T cell responses against PPI1-18, PPI7-19 and PPI31-49, the first two belonging to the leader sequence of PPI, and GAD65271-285 and GAD65431-450, were found in HLA-DR4, -DQ8 and -DR3, -DQ2 T1D children. These data show that cryptic epitopes from the leader sequence of the PPI and GAD65271-285 and GAD65431-450 peptides might be among the critical antigenic epitopes eliciting the primary autoreactive responses in the early phases of the disease. These results may have implications in the design of immunogenic PPI and GAD65 peptides for peptide-based immunotherapy.